Partial Purification, Characterisation and Gene Detection of Protease by Lacticaseibacillus paracasei IN17 from Inasua - Naurah Fikriani Zawawi,; Nisa Rachmania Mubarik,; Laksmi Ambarsari, (Tropical Life Sciences Research, 2025)
Enzymes are functional proteins that accelerate chemical reactions and reduce the activation energy. Lacticaseibacillus paracasei, a lactic acid bacterium, is widely used as a probiotic supplement in the food industry. L. paracasei strain IN17 was isolated from Inasua, Indonesian fish fermentation products. It produces an extracellular protease that hydrolyses peptide bonds to produce peptides or amino acids. It is important to characterise bacteria that produce protease to know their activity and potency. This study aims to purify, characterise and detect the protease-encoding gene from L. paracasei. Isolates that have been identified were tested qualitatively by measuring the proteolytic index. The optimal production was known for two incubation treatments with static and dynamic conditions. The crude extract was precipitated with ammonium sulfate in the concentration range of 0%–80% (w/v). Enzyme activity characterisation was carried out based on optimum pH and temperature, the effect of cation metal, inhibitor and protease kinetics. The static condition had higher growth and protease-specific activity than the dynamic condition, which were 0.137 U/mg and 0.054 U/mg, respectively, at 18 h of production. Ammonium sulfate saturation at a concentration of 20% (w/v) resulted in a protease purity 7.36. The optimal activity of crude extract and precipitated protease were at pH 7 and 6, respectively. Both crude extract and precipitated protease have an optimal temperature at 30°C, activated by Mn cofactor and inhibited by EDTA with >50% inhibition percentage. This protease represents a metalloprotease. The gene encoding protease (prtP) was successfully amplified with ~685 bp visualised in an agarose gel 1% (w/v).